2019
DOI: 10.1016/j.dadm.2019.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Full exploitation of high dimensionality in brain imaging: The JPND working group statement and findings

Abstract: Advances in technology enable increasing amounts of data collection from individuals for biomedical research. Such technologies, for example, in genetics and medical imaging, have also led to important scientific discoveries about health and disease. The combination of multiple types of high-throughput data for complex analyses, however, has been limited by analytical and logistic resources to handle high-dimensional data sets. In our previous EU Joint Programme–Neurodegenerative Disease Research (JPND) Workin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Of particular interest, we found that genetic loci affecting brain morphology show enrichment for developmentally regulated genes 13 and human-specific regulatory elements 26,27 . Ongoing efforts are beginning to map these genetic effects at a finer-grained spatial resolution using shape analysis, surface-and voxel-based analyses [28][29][30][31] . Moving beyond the mass univariate methods, which analyze each brain measure separately, ENIGMA has begun to use multivariate methods to meet the challenge of quantifying the complex relationships between brain networks-or 'connectomes'-and the genome [32][33][34] .…”
Section: Uncovering the Genetic Basis Of Brain Morphometric Variationmentioning
confidence: 99%
“…Of particular interest, we found that genetic loci affecting brain morphology show enrichment for developmentally regulated genes 13 and human-specific regulatory elements 26,27 . Ongoing efforts are beginning to map these genetic effects at a finer-grained spatial resolution using shape analysis, surface-and voxel-based analyses [28][29][30][31] . Moving beyond the mass univariate methods, which analyze each brain measure separately, ENIGMA has begun to use multivariate methods to meet the challenge of quantifying the complex relationships between brain networks-or 'connectomes'-and the genome [32][33][34] .…”
Section: Uncovering the Genetic Basis Of Brain Morphometric Variationmentioning
confidence: 99%